2022
DOI: 10.1093/ecco-jcc/jjac108
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Ustekinumab in Elderly Patients with Crohn’s Disease: Real World Evidence From the ENEIDA Registry

Abstract: Background and Aims Clinical trials and real-life studies with ustekinumab in Crohn's disease (CD) have shown a good efficacy and safety profile. However, these data are scarcely available in elderly patients. Therefore, we aim to assess the effectiveness and safety of ustekinumab in elderly patients with CD. Methods Elderly patients (>60 years old) from the prospectively maintained ENEIDA registry treated with ustekin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
1
15
0
1
Order By: Relevance
“…Among the 63 publications, 10‐72 58 were journal articles and 5 were international conference abstracts. Two conference abstracts 71,72 were replaced by subsequent published articles found in our search.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 63 publications, 10‐72 58 were journal articles and 5 were international conference abstracts. Two conference abstracts 71,72 were replaced by subsequent published articles found in our search.…”
Section: Resultsmentioning
confidence: 99%
“…Real-world data suggest VDL and UST to be equally safe and effective in young and elderly patients with CD who are biologics naïve 49 50. Taking account of the increased risk of infection on using anti-TNF drugs, especially when given along with concomitant IMMs,39 UST or VDL could be prescribed as first-line biological therapy, at least in frail patients with CD 49 50. However, it should be noted that comparative safety data between UST and VDL and anti-TNF drugs are still scarce.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, an SLR also revealed that UST was an effective option for treating EIMs, especially dermatological and rheumatological manifestations 105. In frail patients with CD, VDL would be preferred by the experts,106 107 whereas UST could also be a reasonable option according to available data in this patient subgroup 49 50 108. Promising results have been reported on using UST in patients with CD and skin manifestations 109 110…”
Section: Resultsmentioning
confidence: 99%
“…These results are clearly different to ours, perhaps, because our population is bio-naïve. In another Spanish study from the ENEIDA registry by Casas-Deza et al 26 Safety is one of the main attributes of ustekinumab. In our study, only 10 adverse events were reported during follow-up, and only four of them led to treatment discontinuation.…”
Section: Discussionmentioning
confidence: 96%
“…These results are clearly different to ours, perhaps, because our population is bio-naïve. In another Spanish study from the ENEIDA registry by Casas-Deza et al 26 published in 2022 and including a considerable number of patients, the effectiveness and safety of ustekinumab were assessed in elderly (>60 years, n = 212) versus young (<60 years, n = 436) patients. Every elderly patient was matched with two young controls under 60 years of age, according to anti-TNF use and smoking habit; however, comorbidities and rate of complicated disease (structuring or fistulizing) were more common in elderly patients.…”
Section: Discussionmentioning
confidence: 99%